Common Property and Local Development. Research Elements for Friuli Venezia Giulia (Italy) - Maurizio Daici (Revue de Géographie Alpine)
A few decades ago, common land ownership was viewed as a legal institution of the past, irreconcilable with the modern capitalistic economy, that required private ownership. With this opinion, in 1927, the legislator mainly acted to get the agricultural properties free from common uses (grazing, gathering wood, etc.) and to reduce the extensions of the properties opened to a shared utilisation, by putting them at the same time under the authority of the municipalities. However, from the 1950s, law provisions for special measures in favour of mountain areas indicated the common properties (meadows, forests, farm buildings) as valuable resources for development initiatives, not only in traditional activity sectors (especially in the touristic sector). Besides, they protected the self-government of some typologies of shared ownership. Finally, in 2017, a law stated the principle of self-government of all common ownerships and the concept that these ownerships are local development elements. Nevertheless, for a role in the local development, the representatives of the common ownerships have to change their interests from the mere conservation of their assets to targets of social and economic development of the entire territory which they live in, and to overcome, if necessary, the suspiciousness of regional and municipal institutions which experiences in Friuli Venezia Giulia show.